Isópodos (Crustacea: Peracarida) de un arrecife del Caribe de Costa Rica - Breedy, Odalisca (Universidad de Costa Rica, 1995)
Marine isopods from Cahuita, Limón, Costa Rica were collected in artificiai habitats placed in three areas of a coral reef between November 1983 and December 1985: Cirolana parva. Paracersis caudata. Excorallana tricomis. Mesanthura paucidens. Colanthura sp., Gnathia sp., and Bagatus serricaudus. Illustrations are included as a guide for identification.